A SCIENTIST'S PORTFOLIO AS A TOOL FOR INTEGRATION INTO THE INTERNATIONAL EDUCATIONAL AND SCIENTIFIC AREA (Innovative professional education, 2022)
In the context of global processes and trends, the spheres of the scientist’s activity which is aimed at improving the quality of domestic education and developing scientific cooperation in the international educational and scientific space were analysed. The structure of the scientist's portfolio was proposed. It will allow to structure information about the results and prospects of the researcher's educational and scientific activities, as well as to respond effectively and quickly to the requests of domestic and foreign partners regarding the development of educational, scientific and cultural areas of cooperation.
Keywords: globalization, educational and scientific activity, international cooperation, internationalization, international projects, sustainable development, innovations